2021
DOI: 10.1016/j.isci.2021.102535
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae pneumolysin and neuraminidase A convert high-density lipoproteins into pro-atherogenic particles

Abstract: High-density lipoproteins (HDLs) are a group of different subpopulations of sialylated particles that have an essential role in the reverse cholesterol transport (RCT) pathway. Importantly, changes in the protein and lipid composition of HDLs may lead to the formation of particles with reduced atheroprotective properties. Here, we show that Streptococcus pneumoniae pneumolysin (PLY) and neuraminidase A (NanA) impair HDL function by causing chemical and structural modifications of HDLs. The proteomic, lipidomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…HDL was isolated from plasma of iNPH patients with apoE23 ( n = 2) or apoE44 ( n = 2) genotype by sequential flotation in an ultracentrifugation using potassium‐bromide for density adjustment as previously described (Syed et al , 2021). The methodology of the preparations was as follows: Plasma VLDL and LDL ( d < 1.063 g/ml) and total HDL (1.063 < d < 1.210 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…HDL was isolated from plasma of iNPH patients with apoE23 ( n = 2) or apoE44 ( n = 2) genotype by sequential flotation in an ultracentrifugation using potassium‐bromide for density adjustment as previously described (Syed et al , 2021). The methodology of the preparations was as follows: Plasma VLDL and LDL ( d < 1.063 g/ml) and total HDL (1.063 < d < 1.210 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…48,49 In mouse and rabbit models, infiltration of C pneumoniae into the atherosclerotic environment lead to the acceleration of plaque progression and resulted in a more unstable plaque phenotype and in human macrophages, induced the secretion of matrix metalloproteinase-9. [50][51][52][53][54][55] Also, pneumolysin-an important virulence factor released by S pneumoniae that can translocate from the lungs and into circulation-can convert highdensity lipoprotein into proatherogenic molecules in humans, 56 in addition to stimulating cardiac injury in a mouse model of pneumonia. 57 However, the detection of pathogens in atherosclerotic plaques or myocardium of humans in the context of acute pneumonia or systemic infections has not been reported.…”
Section: Relationship Between Pneumonia and Cardiovascular Disease: E...mentioning
confidence: 99%
“…A third potential mechanism of Ply-mediated cardiotoxicity, albeit unexplored in the setting of experimental pneumococcal infection, involves the interaction of Ply and pneumococcal neuraminidase A (NanA) with high-density lipoproteins [ 77 ]. In this study, Syed et al observed that exposure of HDL particles to the combination of Ply and NanA in vitro resulted in significant alterations to the sialic acid, protein, and lipid composition of the lipoproteins.…”
Section: Role Of Pneumolysin In Cardiac Dysfunction During Severe Pne...mentioning
confidence: 99%
“…In this study, Syed et al observed that exposure of HDL particles to the combination of Ply and NanA in vitro resulted in significant alterations to the sialic acid, protein, and lipid composition of the lipoproteins. These alterations in molecular structure were associated with oxidative damage and pro-inflammatory activity, as well as increased complement activity, resulting in increased pro-atherogenic potential [ 77 ].…”
Section: Role Of Pneumolysin In Cardiac Dysfunction During Severe Pne...mentioning
confidence: 99%